Plastics in medical devices for cardiovascular applications - Padsalgikar, Ajay D. (PDL handbook series., 2017)
Plastics in Medical Devices for Cardiovascular Applications enables designers of new cardiovascular medical devices to make decisions about the kind of plastics that can go into the manufacture of their device by explaining the property requirements of various applications in this area, including artificial valves, lead insulation, balloons, vascular grafts, and more.